Edukasi Manfaat Lilin Aromaterapi Lavender untuk Meningkatkan Kualitas Tidur Ibu Hamil di BPM Muzilatul Nisma - Selpyani Sinulingga; Sirly Patriani (Sekolah Tinggi Ilmu Kesehatan Baiturrahim Jambi, 2023)
Aromatherapy is a healing therapy that involves the use of pure essential oils distilled from various parts of plants, flowers, and trees, each of which contains therapeutic properties. One form of aromatherapy preparation is aromatherapy candles. Aromatherapy candles are an object that can provide a calming effect. Essential oil from lavender flower extract as aromatherapy that gives a relaxing, anti-neurodepressive and sedating effect that is beneficial for pregnant women who experience insomnia, reduce anxiety levels and, increase levels of alertness. This therapy is recommended for pregnant women to help minimize discomfort during pregnancy, especially reducing the problem of sleep disorders. The purpose of this activity is to increase knowledge about the benefits of aromatherapy candles to improve the quality of sleep of pregnant women. The target of the implementation of this activity was carried out in trimestester II and III pregnant women. The form of activities is in the form of providing education with the lecture method with leaflet media and to see the increase in knowledge is done by conducting pre-test and post-test. The results obtained were before being given education the level of knowledge of pregnant women was 64.75% and after being given education the mother's knowledge increased to 93.6%, so it can be concluded that there was an increase in knowledge by 28.85%. With this educational activity, it is hoped that an increase in knowledge and an increase in the mother's sense of comfort during pregnancy will be achieved